2006
DOI: 10.1038/sj.bjc.6602958
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of multidrug resistance gene expression on the management of breast cancer in the context of adjuvant therapy based on a series of 171 patients

Abstract: Study of the prognostic impact of multidrug resistance gene expression in the management of breast cancer in the context of adjuvant therapy. This study involved 171 patients treated by surgery, adjuvant chemotherapy7radiotherapy7hormonal therapy (mean follow-up: 55 months). We studied the expression of multidrug resistance gene 1 (MDR1), multidrug resistance-associated protein (MRP1), and glutathione-S-transferase P1 (GSTP1) using a standardised, semiquantitative rt -PCR method performed on frozen samples of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
3
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 45 publications
2
28
3
1
Order By: Relevance
“…This is in concordance with previous reports where the absence of GSTP1 protein expression correlated with improved survival in invasive breast cancer samples (10,29) and colorectal cancer (11). In contrast, other studies related low GSTP1 expression or GSTP1 hypermethylation to decreased survival and poor prognosis (15,30). The difference between the results might be attributable to the molecular diversity in human breast cancer as well as differences in the received adjuvant therapy.…”
Section: Cancer Researchcontrasting
confidence: 49%
“…This is in concordance with previous reports where the absence of GSTP1 protein expression correlated with improved survival in invasive breast cancer samples (10,29) and colorectal cancer (11). In contrast, other studies related low GSTP1 expression or GSTP1 hypermethylation to decreased survival and poor prognosis (15,30). The difference between the results might be attributable to the molecular diversity in human breast cancer as well as differences in the received adjuvant therapy.…”
Section: Cancer Researchcontrasting
confidence: 49%
“…Similarly, the expression of MRP1 was associated with an increased risk of failure in cases with small tumors, in node-negative tumors and in node-positive patients in a retrospective series of patients with localized breast cancer, who received adjuvant systemic chemotherapy based on MRP1 substrates such as cyclophosphamide and methotrexate (26). Nevertheless, another study found a statistically significant relationship of GST, but not MRP1, with disease-free survival in patients with localized breast cancer treated with adjuvant chemotherapy (27).…”
Section: Discussionmentioning
confidence: 93%
“…However, to date the results are still somewhat controversial and may vary from population to population. (Gilbert et al, 1993;Silvestrini et al, 1997;Buser et al, 1997;Helzlsouer et al, 1998;Millikan et al, 2000;Mitrunen et al, 2001;Gudmundsdottir et al, 2001;Huang et al, 2003;Egan et al, 2004;Sreenath et al, 2005;Moureau-Zabotto et al, 2006;Unlu et al, 2008;Saxena et al, 2009;Arun et al, 2010;Pongtheerat et al, 2011;Zhang et al, 2011;Ramalhinho et al, 2011;Aguiar et al, 2012;Ramalhinho et al, 2012;Saxena et al, 2013;Khabaz, 2014;Rodríguez et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Many previous studies revealed GSTP1 polymorphism has no correlation with clinical and pathologic tumor characteristics (Buser et al, 1997;Huang et al, 2003) only a few studies showed an inverse correlation with ER (Gilbert et al, 1993;Silvestrini et al, 1997;Moureau-Zabotto et al, 2006). Furthermore, two studies of Pongtheerat and colleagues reported that GSTP1 polymorphism was unrelated to increased risk of breast cancer, but found an inverse relationship between GSTP1 genotype and progesterone receptor protein (Pongtheerat et al, 2009;Pongtheerat et al, 2011), and positive correlation with better tumor differentiation and grade (Cairns et al, 1992;Haas et al, 2006).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation